Altered Regulation of Renal Acid Base Transporters in Response to Ammonium Chloride Loading in Rats - Kim, Eun Young (The Korean Physiological Society and The Korean Society of Pharmacology, 2012)
The role of the kidney in combating metabolic acidosis has been a subject of considerable interest for many years. The present study was aimed to determine whether there is an altered regulation of renal acid base transporters in acute and chronic acid loading. Male Sprague-Dawley rats were used. Metabolic acidosis was induced by administration of NH(4)Cl for 2 days (acute) and for 7days (chronic). The serum and urinary pH and bicarbonate were measured. The protein expression of renal acid base transporters [type 3 Na(+)/H(+) exchanger (NHE3), type 1 Na(+)/HCO(3)(-) cotransporter (NBC1), Na-K(+) ATPase, H(+)-ATPase, anion exchanger-1 (AE-1)] was measured by semiquantitative immunoblotting. Serum bicarbonate and pH were decreased in acute acid loading rats compared with controls. Accordingly, urinary pH decreased. The protein expression of NHE3, H(+)-ATPase, AE-1 and NBC1 was not changed. In chronic acid loading rats, serum bicarbonate and pH were not changed, while urinary pH was decreased compared with controls. The protein expression of NHE3, H(+)-ATPase was increased in the renal cortex of chronic acid loading rats. These results suggest that unaltered expression of acid transporters combined with acute acid loading may contribute to the development of acidosis. The subsequent increased expression of NHE3, H(+)-ATPase in the kidney may play a role in promoting acid excretion in the later stage of acid loading, which counteract the development of metabolic acidosis.